Residual stress distribution of a locally and inductively quenched and tempered 50CrMo4 steel analysed by synchrotron transmission techniques. (September 2022) - Jászfi, V.; Prevedel, P.; Raninger, P.; Todt, J.; Mevec, D.; Godai, Y.; Maawad, E.; Ebner, R.
Graphical abstract: Highlights: Residual stress distribution in locally quenched and tempered 50CrMo4 steel using synchrotron transmission techniques Relationship between residual stresses, retained austenite content and hardness for two specific local heat treatment states Macrosegregations reduce the magnitude of residual stresses and retained austenite content in the quenched 50CrMo4 steel Geometry and quenching rate have a greater influence on the residual stresses than the chemical composition of 50CrMo4 steel Abstract: This work investigates the in-depth residual stress distribution and retained austenite content in plates that were wire eroded from one locally quenched and one locally quenched-tempered 50CrMo4 cylinders by the means of high-energy X-Ray synchrotron transmission techniques. The main challenge was to interpret the results from all diffraction angles to obtain meaningful validation data for future computer simulations of induction hardening and tempering. The results were discussed in relation to hardness distribution. With the help of the applied measurement technique, even the effects of macro-segregation near the longitudinal sample axis can be detected. In inductively heated and quenched cylindrical specimens of 50CrMo4 specimens, macro-segregations near the longitudinal sample axis lead to a reduced retained austenite content, which shifts the axial stresses towards tensile stresses. Comparing the results with those from the literature, it can be seen that variations in the chemical composition of the sample within the specification range of the steel grade have less influence on the residual stress distribution in the induction hardened samples than the sample geometry and/or the quenching rate.